Rapid Response to the Combination of Lenvatinib and Sintilimab in a Pancreatic Acinar Cell Carcinoma Patient With Elevated Alpha-Fetoprotein: A Case Report - Qin, Lanqun; Shen, Jie; Yang, Yueling; Zou, Zhengyun (Frontiers in Oncology, 2021)
A 48-year old woman was diagnosed with metastatic pancreatic acinar cell carcinoma (PACC) and with a marked elevation in alpha-fetoprotein (AFP), this being a recognized but uncommon feature of PACC. As she refused chemotherapy, the combined therapy of lenvatinib and sintilimab (lenvatinib 8 mg, orally, qd; and sintilimab 100 mg, intravenous glucose tolerance test, q21d) was given, which conferred significant tumor shrinkage and long progression-free survival (>21 months). This study is the first report and description of a PACC demonstrating favorable response to the combination therapy of an antiangiogenic agent and immunotherapy.